(untitled) (International Journal of Food and Nutritional Sciences, 2023)
Food poisoning happens all throughout the world. Numerous toxins that cause particular food poisoning syndromes are no longer confined to remote geographical areas. It is likely that a patient will present to any emergency department with the clinical symptoms of food poisoning given the increase in travel and the convenience of carrying food products. The ability to identifyparticular food poisoning syndromes enables emergency medical personnel to promptly begin the necessary treatment as well as to alert health departments and so stop further occurrences of food poisoning. This article analyses a number of probable food-borne toxins and discusses the mechanisms of toxicity, anticipated clinical manifestations, and standard treatments for each agent. Only three bacterial species are considered important causes of the intoxication type of food poisoning. These are Bacillus cereus, Clostridium botulinum and Staphylococcus aureus, all of which are capable of causing illness by producing toxins in food. There are several other species of Bacillus and Clostridium that have been reported to produce pre-formed toxins in food, such as B. licheniformis and Cl. butyricum, but these are uncommon and not considered further here.